Fast Hugs with Intensive Care Unit - Nimet Şenoğlu; Işıl Köse; Çiler Zincircioğlu; Rıza Hakan Erbay (Galenos Yayinevi, 2014)
Mnemonics are commonly used in medical procedures as cognitive aids to guide clinicians all over the world. The mnemonic 'FAST HUG' (Feeding, Analgesia, Sedation, Thromboembolic prophylaxis, Head-of-bed elevation, stress Ulcer prevention, and Glycemic control) was proposed almost ten years ago for patient care in intensive care units and have been commonly used worldwide. Beside this, new mnemonics were also determined for improving routine care of the critically ill patients. But none of this was accepted as much as "FAST HUGS". In our clinical practice we delivered an another mnemonic as FAST HUGS with ICU (Feeding, Analgesia, Sedation, Thromboembolic prophylaxis, Head-of-bed elevation, Stress ulcer prevention, and Glucose control, Water balance, Investigation and Results, Therapy, Hypo-hyper delirium, Invasive devices, Check the daily infection parameters, Use a checklist) for checking some of the key aspects in the general care of intensive care patients. In this review we summarized these mnemonics.